Assessment of hairy roots induction in Solenostemon scutellarioides leaves by different strains of Agrobacterium rhizogenes - Mohd. Saleh, Norihan; Thuc, Le Vinh (Academic Journals, 2009)
Hairy roots of Solenostemon scutellarioides were induced by inoculation of leaf explants with Agrobacterium rhizogenes strains TR 105, LBA 9402, 8196 and ATCC 15834. These strains showed different abilities to induce hairy root formation on the leaf explants. Assessment of the plant’s susceptibility to the different strains of A. rhizogenes showed that strains ATCC 15834, TR 105, LBA 9402, and 8196 produced 56.3, 25.5, 21.5 and 13.8% transformation efficiencies, respectively. Acetosyringone was found to be useful for the enhancement of hairy roots formation in S. scutellarioides.